Evaluasi Kepatuhan Penggunaan Obat Anti Tuberkulosis Pada Pasien TBC Anak Di Klinik Ananda Siaga Kecamatan Cianjur Periode Januari-September Tahun 2024: Evaluation of Compliance with the Use of Anti-Tuberculosis Drugs in Pediatric Tuberculosis Patients at the Ananda Siaga Clinic, Cianjur Sub-District, January - September Period In 2024 - Eneng Puspita Wati; Imam Syafi'i; Julia Totong (UIMA Press, 2025)
Tuberculosis (TB) is an infectious disease that remains a major global health problem and the second leading cause of death after HIV/AIDS. It is caused by Mycobacterium tuberculosis. Children with TB are increasingly susceptible to infection as the number of adult TB cases continues to rise. This study aimed to evaluate adherence to anti-tuberculosis drug (OAT) use among children with TB at Ananda Siaga Clinic, Cianjur District. This research employed a non-experimental quantitative approach with a cross-sectional design. A total of 189 samples were obtained through purposive sampling from 360 patients during the period of January–September 2024. Adherence levels were measured using the Morisky Medication Adherence Scale (MMAS-8). The results showed that the accuracy of diagnosis, drug selection in both intensive and continuation phases, and frequency of OAT administration reached 100%. Dose accuracy was recorded at 75.13%. The treatment adherence level was high, with 82% of children being adherent. However, there was no significant relationship between adherence level and drug use (p = 0.094). In conclusion, TB treatment in children at Ananda Siaga Clinic was in accordance with the 2016 National Tuberculosis Control Guidelines.